Evaluation of systemic oxidant/antioxidant status and paraoxonase 1 enzyme activities in psoriatic patients treated by narrow band ultraviolet B phototherapy. (1st September 2013) - Pektas, S.D.; Akoglu, G.; Metin, A.; Neselioglu, S.; Erel, O.
Abstract : Objectives Ultraviolet B is a potent oxidative stress (OS) inducer in the skin; however, there are no data about the systemic oxidative effect of narrow band ultraviolet B (NB-UVB) phototherapy. In this study, we aimed to investigate the change in the OS status of psoriatic patients who were treated by NB-UVB phototherapy and to determine the relationships between OS, psoriasis severity, and systemic inflammatory condition. Methods Twenty-four psoriatic patients were treated with a total of 30 sessions of NB-UVB irradiation. Psoriasis area and severity index (PASI), serum levels of high sensitive C-reactive protein (hsCRP), total antioxidant status (TAS), total oxidant status (TOS), the oxidative stress index (OSI), serum paraoxonase (PON), and arylesterase (ARE) activities before and after NB-UVB therapy were determined. Results PASI scores significantly decreased after NB-UVB therapy ( P = 0.001). The pre- and post-treatment hsCRP and TAS levels were similar ( P = 0.253 and 0.301, respectively). TOS and OSI values significantly increased after phototherapy (both P < 0.001). PON and ARE activities did not change after treatment (both P > 0.05). There was no correlation between PASI and hsCRP, TAS, TOS, OSI, PON, and ARE values ( P > 0.05). Conclusion A systemic OS may emerge in psoriatic patients treated by NB-UVB phototherapy.